2019
DOI: 10.1007/s42773-019-00028-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and morphology of biochars as affected by feedstock sources and pyrolysis temperatures

Abstract: Feedstock sources and pyrolysis temperatures affect the physicochemical and morphological properties of biochars. We evaluated biochars derived from switchgrass (SGB) and poultry litter (PLB) pyrolyzed at 350 °C (SGB350, PLB350) and 700 °C (SGB700, PLB700) to identify their potential ability in improving soil health. Except for SGB350, the pH of biochars was high (> 10.0) and can be used as an amendment in acid soils. PLB700 had higher mineral content and nutrient availability due to its higher ash content (te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 51 publications
1
32
1
Order By: Relevance
“…A significant decrease in the transfer factor values (TF) of PTMs (Zn, Pb, and Cd) from ryegrass roots to ryegrass shoots when evaluating PLB and SGB additions to a multi-metal contaminated soil was found by [22], and that the PLB was more efficient in such reduction than SGB. This was probably a consequence of their higher pH, CEC, specific surface area (SSA), and stronger buffering capacity as reported by [23], which resulted in the higher efficiency of PLB in decreasing PTMs uptake, as highlighted by the higher decrease of the bioconcentration factor (BCF = [PTMs in shoots/PTMs concentration in soil]) as PLB application rates increased. Figure 5 (and Figure 3) briefly summarizes such findings and highlights the PTMs immobilization as a function of two feedstocks derived-biochar application rates.…”
Section: The Effect Of Biochar Feedstock Sources On Ptms Phytoavailabilitymentioning
confidence: 88%
See 1 more Smart Citation
“…A significant decrease in the transfer factor values (TF) of PTMs (Zn, Pb, and Cd) from ryegrass roots to ryegrass shoots when evaluating PLB and SGB additions to a multi-metal contaminated soil was found by [22], and that the PLB was more efficient in such reduction than SGB. This was probably a consequence of their higher pH, CEC, specific surface area (SSA), and stronger buffering capacity as reported by [23], which resulted in the higher efficiency of PLB in decreasing PTMs uptake, as highlighted by the higher decrease of the bioconcentration factor (BCF = [PTMs in shoots/PTMs concentration in soil]) as PLB application rates increased. Figure 5 (and Figure 3) briefly summarizes such findings and highlights the PTMs immobilization as a function of two feedstocks derived-biochar application rates.…”
Section: The Effect Of Biochar Feedstock Sources On Ptms Phytoavailabilitymentioning
confidence: 88%
“…The role of biochar in improving soil pH, organic carbon (OC), and CEC was also highlighted by [16]. Moreover, biochar can immobilize PTMs (immobilization is the reduction of the potential migration of PTMs to plants, or reduction of phytoavailability) such as cadmium (Cd), lead (Pb), and zinc (Zn) and thereby to reduce the phytoavailability of PTMs (concentration of PTMs in plant parts, or contents of PTMs in soils available to plants) to plants in contaminated soils, notably because it raises the soil pH [18,22] and increases CEC and OC [23]. Many studies also found biochar application promotes the ability to remove organic contaminants [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Switchgrass-and poultry litter-derived biochars are referred to as SGB and PLB, respectively. The biochars coarse materials were ground with a mortar and pastel gently before sieved through 1 mm for further physicochemical analyses [24] and through 0.25 mm for the potting experiment. A full characterization of SGB and PLB including all physicochemical properties such as moisture, ash content, particle-size distribution, elemental composition, surface functional groups, chemical attributes, specific surface area, cation exchange capacity (CEC), and morphology can be found in [24].…”
Section: Biochar Production and Characteristicsmentioning
confidence: 99%
“…The biochars coarse materials were ground with a mortar and pastel gently before sieved through 1 mm for further physicochemical analyses [24] and through 0.25 mm for the potting experiment. A full characterization of SGB and PLB including all physicochemical properties such as moisture, ash content, particle-size distribution, elemental composition, surface functional groups, chemical attributes, specific surface area, cation exchange capacity (CEC), and morphology can be found in [24]. For this study, it is useful to emphasize the ash, total carbon (TC), total nitrogen (TN), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sulfur (S) contents, as presented in Table 1.…”
Section: Biochar Production and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation